A high sucrose diet modifies brain oxylipins in a sex-dependent manner. (November 2022) - Norman, Jennifer E.; Nuthikattu, Saivageethi; Milenkovic, Dragan; Rutledge, John C.; Villablanca, Amparo C.
Highlights: Consumption of a high sucrose diet alters the brain free oxylipin profile. The oxylipins changed by a high sucrose diet differ between sexes. Regardless of diet, there are sex differences in the brain free oxylipin profile. Abstract: Background: Oxylipins have been implicated in many biological processes and diseases. Dysregulation of cerebral lipid homeostasis and altered lipid metabolites have been associated with the onset and progression of dementia. Although most dietary interventions have focused on modulation of dietary fats, the impact of a high sucrose diet on the brain oxylipin profile is unknown. Methods: Male and female C57BL/6J mice were fed a high sucrose diet (HSD, 34%) in comparison to a control low sucrose diet (LSD, 12%) for 12 weeks beginning at 20 weeks of age. The profile of 53 free oxylipins was then measured in brain by ultra-high performance liquid chromatography tandem mass spectrometry. Serum glucose and insulin were measured enzymatically. We first assessed whether there were any effects of the diet on the brain oxylipin profile, then assessed for sex differences. Results: There were no differences in fasting serum glucose between the sexes for mice fed a HSD or in fasting serum insulin levels for mice on either diet. The HSD altered the brain oxylipin profile in both sexes in distinctly different patterns: there was a reduction in three oxylipins (by 47–61%) and an increase in one oxylipin (16%) all downstream of lipoxygenase enzymes in males and a reduction in eight oxylipins (by 14–94%) mostly downstream of cyclooxygenase activity in females. 9-oxo-ODE and 6-trans-LTB4 were most influential in the separation of the oxylipin profiles by diet in male mice, whereas 5-HEPE and 12-HEPE were most influential in the separation by diet in female mice. Oxylipins 9‑hydroxy-eicosatetraenoic acid (HETE), 11-HETE, and 15-HETE were higher in the brains of females, regardless of diet. Conclusion: A HSD substantially changes brain oxylipins in a distinctly sexually dimorphic manner. Results are discussed in terms of potential mechanisms and links to metabolic disease. Sex and diet effects on brain oxylipin composition may provide future targets for the management of neuroinflammatory diseases, such as dementia.